Utilisation of Commonwealth Studies Literature: Problems and Prospects - Slew Mun, Khoo (Journal of Information and Knowledge, 1982)
This paper presents a survey of readers with special reference to the use of literature on commonwealth studies in the library of the University of Malaya. The study specifies the concept of utilization and the contents of commonwealth studies. Analyses the collection of monographs periodical literature and microforms available in the University of Malaya. Projects the future developments of collection and usage of documents in common wealth studies. Highlights the amorphous nature of common wealth studies. Highlights the main difficulties faced by users of such materials such as accessibility to archival materials, break-up of continuity of periodical publication due to inadequate funding, and the problems due to delay in updating the file of information and information retrieval tools. Presents the details of the methodology followed and the questionnaire used.